ANALISIS PENGARUH KUALITAS PRODUK, PROMOSI, KUALITAS PELAYANAN DAN LOKASI TERHADAP LOYALITAS PELANGGAN - Mahadyka Agung Prasetyo; Rois Arifin (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to determine the effect of Quality Product, Promotion, Quality Service and Location on loyality customer SCH Clothing Malang, the sample of this study is students boarding in Sudimoro. For collecthing the data used questionnaires to students boarding in Sudimoro, to analyze the data used validity test, reliability test, normality test, multiple linear analyze, statistical test F and statisical test t, coefficient determination test in IBM Statistical Package for Social Science (SPSS) 16.0 version. The result of this study have a significant positive effect on loyality customer, quality product on loyality customer, promotion on loyality customer, quality servic on loyality customer and location on loyality customer. In conclussion Simultaneously test product quality, promotion, service quality and location have an effect on customer loyalty, then in a partial test of product quality, promotion, service quality and location has an effect on customer loyalty.Keywords: Quality Product; Promotion; Quality Service; Location